Analisis Kesesuaian Lahan Untuk Padi Sawah Kecamatan Demak Kabupaten Demak - Romadhon, Fadkur, Ir. Taryono,M.Si (2017)
Rice is the food ingredients that are in the process of becoming of rice. And over the rising human population also foodstuffs it take more and more, the need for planting or processing a good rice to meet the ever increasing food needs as the population of its in habitants. In this research has two goals : (1) Determine the suitability of land for paddy rice fields in district of Demak. And (2) Evaluationof the factors that affect the suitability of the land in district of Demak. The methods used in this research is a survey method include observation, measurement, recording and systematically for warded with field data analysis laboratory. Results of the research are matching is comparing class suitability of land for rice plant with the characteristics of the land in the area of research. Besed on data from field and laboratory data, the research on land suitability results get entered in a class or appropriate marginal (S3) for paddy rice. For drainage of the border there is on the whole a unit of land ara of research. For drainage nad delimiter field is present on the land unit Gr 3 S Sw. And delimiters for drainage and salinity is present on the land unit Gr 1 S Tg and Gr 2 S Tg. Result obtained after a unit of land and land suitability classes in the area of research and then presented in a mapping.